MANAJEMEN SARANA DAN PRASARANA SEKOLAH ALAM - Hakim, Luqmanul (JMSP (Jurnal Manajemen dan Supervisi Pendidikan), 2016)
facilities and infrastructure of nature with through several functions, namely, planningfacilities and infrastructure nature, provision of school facilities and infrastructure of nature,an inventory of school facilities and infrastructure nature, maintenance of facilities andinfrastructure of the school of nature, the use of facilities and infrastructure nature school,and discuss the effectiveness of the use of school facilities and infrastructure nature. Researchqualitative approach with case study design. The technique of collecting data by interview,observation, documentation and then the data analysis is done through data reduction , thedisplay of the data and the verification data. The findings of the research include, functioningschool facilities and infrastructure management nature, planning, procurement, inventory,maintenance, use of facilities and infrastructure as well as the effectiveness of the use ofschool facilities and infrastructure nature.Keywords : management of facilities and infrastructure, natural schoolAbstrak : Penelitian ini bertujuan untuk mengkaji, mengetahui dan menjelaskan manajemensarana dan prasarana sekolah alam melakui beberapa fungsi yaitu, perencanaan sarana danprasarana alam, pengadaan sarana dan prasarana sekolah alam, inventarisasi sarana danprasarana sekolah alam, pemeliharaan sarana dan prasaran sekolah alam, pengunaan saranadan prasarana sekolah alam, dan membahas keefektifan pengunaan sarana dan prasaranasekolah alam. Penelitian ini menggunakan pendekatan kualitatif dengan rancangan penelitianstudi kasus. Teknik pengumpulan data dengan wawancara, observasi, dokumentasi kemudiananalisis data dilakukan melalui reduksi data, penampilkan data dan verifikasi data. Temuanpenelitian meliputi, fungsi manajemen sarana dan prasarana sekolah alam, perencanaan,pengadaan, inventarisasi, pemeliharaan, penggunaan sarana dan prasarana serta keefektifanpenggunaan sarana dan prasarana sekolah alam.Kata Kunci : manajemen sarana dan prasarana, sekolah alam